2004
DOI: 10.1016/j.jchromb.2004.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Separation and isolation methods for analysis of the active principles of Sho-saiko-to (SST) oriental medicine

Abstract: Sho-saiko-to (SST) was introduced into Japan as an oriental classical medicine from China approximately 1500 years ago, and it is currently the most representative Kampo medicine (traditional Japanese medicine). SST is manufactured in Japan as an ethical drug on a modern industrial scale in which the quality of ingredients is standardized with Good Manufacturing Practices (GMP) regulation. SST is widely used for the treatment of chronic hepatitis. Experimental and clinical studies including multi-center, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 120 publications
0
16
0
Order By: Relevance
“…The herbal preparation of SST is also widely prescribed for the treatment of diverse liver diseases, but without clear understanding of its molecular mechanism [1]. What further complicates the situation is that SST is composed of seven different herbal plants (see Additional file 1: Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…The herbal preparation of SST is also widely prescribed for the treatment of diverse liver diseases, but without clear understanding of its molecular mechanism [1]. What further complicates the situation is that SST is composed of seven different herbal plants (see Additional file 1: Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…So it is well considered that such crude drugs contained in Sho‐saiko‐to may affect the gastrointestinal absorption of the co‐administered drug tolbutamide. Alternatively, Ohtake et al [29] . separated and isolated the active principles of Sho‐saiko‐to, and this Chinese traditional medicine had a huge number of biologically active compounds.…”
Section: Discussionmentioning
confidence: 99%
“…HPLC (high performance liquid chromatography) analysis of pharmacologically active ingredients in SST indicated that the major fractions of SST contain compounds of flavonoid-like structures (e.g. baicalin, baicalein, liquiritin) and triterpene saponins (GL, saikosaponins b1 & b2, ginsenosides Rg1 and Rb1) [55] (Figure 4). Comparative experiments showed that the liver concentrations of the active constituents of SST extract in the liver-injured rats increased significantly after the animals received SST extract, as compared with the groups receiving the respective purified constituents.…”
Section: Biological Activities Of Extracts and Ingredients Of Medicinmentioning
confidence: 99%